İLKÖĞRETİM DİN KÜLTÜRÜ VE AHLAK BİLGİSİ ÖĞRETİM PROGRAMI İLE ORTAOKUL TEMEL DİNİ BİLGİLER DERSİ (İSLAM; I-II) ÖĞRETİM PROGRAMI KAZANIMLARINDAKİ DUYUŞSAL HEDEFLER ÜZERİNE KARŞILAŞTIRMALI BİR ARAŞTIRMA - Çekin, Abdulkadir (Review of the Faculty of Divinity of Amasya University, 2015)
Religious culture and ethics lesson is one of the compulsory courses in Turkey. Together with this lesson, the primary and secondary level students can choose the Quran, the Prophet Muhammad's life and the Basic Religious Information lessons as a selective course. This study is a comparative research on affective objectives of religious culture and ethics lesson and basic religious information course curriculums. In this study, it has been evaluated and comparatively analyzed the affective objectives of religious culture and ethics and basic religious information course curriculums in terms of quantity and quality. At the end of the research, it has reached that religious culture and ethics lesson and basic religious information course aim to gain students cognitive capabilities, religious culture and ethics lesson aims to gain more affective behaviors than basic religious information course.
Keywords: 4. Education